Comparative Legal Lessons from the 2015 and 2024 Riau Islands Gubernatorial Elections - Marsudi; Yani, Achmad (International Journal of Law and Public Policy (IJLAPP), 2025)
This study examines the persistent challenge of regulatory fragmentation in Indonesia’s decentralized electoral governance through a comparative legal analysis of the 2015 and 2024 gubernatorial elections in Riau Islands Province. Using a juridical-comparative approach combined with doctrinal legal analysis and process tracing, the research compares statutory frameworks, institutional coordination, and electoral outcomes. Data were drawn from official regulations, Provincial KPU reports, voter turnout statistics, and budget records. Findings show that while the 2024 election benefited from greater legal coherence than in 2015, unchecked subnational discretion most notably the reduction of polling stations from 4,654 to 3,327 resulted in lower voter turnout (77% to 54%) and reduced accessibility, particularly in remote archipelagic areas. The study argues that both normative misalignment and procedural discretion, when unbounded, undermine electoral inclusiveness and transparency. Theoretically, this article contributes to the discourse on legal pluralism and regulatory coherence by demonstrating how harmonization must integrate both legal standardization and procedural predictability. Practically, it proposes a unified Election Code, “bounded discretion” guidelines, and institutionalized inter-agency coordination to safeguard electoral integrity.